Supervisi Pendidikan Berbasis Adab, Model Pengawasan Akademik Yang Memanusiakan Guru - Roheti (CV JK Riset Publishing Group, 2026)
Educational supervision has predominantly focused on technical and administrative aspects, thereby neglecting the human dimension of teachers as dignified educators. This study aims to design an adab-based educational supervision model that positions teacher-student and supervisor-teacher relationships as ethical and humanistic relations. The research employs a qualitative approach with case study method conducted in three schools in Lampung Province. Data were collected through in-depth interviews, participatory observation, and document analysis. Results indicate that adab-based supervision enhances teachers' self-confidence, strengthens intrinsic motivation, and builds a school culture of mutual respect. It is concluded that humanizing supervision not only improves learning quality but also shapes the character of educational institutions toward civility and dignity.